Eksistensi Hukum Adat Bali dalam Penetapan Dispensasi Perkawinan Anak Akibat Hamil Diluar Nikah: Penetapan Pengadilan No. 209 /Pdt.P/2025/Pn Sgr - Dewa Nyoman Adi Wiraguna; Si Ngurah Ardhya; Ni Luh Wayan Yasmiati (Jurnal Hukum Lex Generalis, 2026)
This research aims to analyze the judges' considerations and the implementation of the best interests of the child principle regarding the marriage dispensation decree Number 209/Pdt.P/2025/PN.Sgr, as well as to examine the existence of Balinese customary law concerning the protection of children's rights related to marriage dispensations. The method employed is normative legal research with statutory and conceptual approaches. The findings indicate that the judges' considerations in granting the marriage dispensation were based on the best interests of the child principle. However, Balinese customary law and national law regarding child marriage remain unaligned, meaning that the granting of marriage dispensations still leaves a loophole for underage marriages. Therefore, harmonization between customary law and national law is required to strengthen the protection of children's rights and prevent early-age marriages.